2013
DOI: 10.1007/s00436-013-3322-6
|View full text |Cite
|
Sign up to set email alerts
|

Cephenemyia stimulator and Hypoderma diana infection of roe deer in the Czech Republic over an 8-year period

Abstract: A survey of naso-pharyngeal and subcutaneous myiasis affecting roe deer (Capreolus capreolus) was conducted in the Czech Republic over an 8-year period (1999-2006). A total of 503 bucks and 264 does from six hunting localities were examined. The sampling area comprised predominantly agricultural lowlands and a mountain range primarily covered by forest. Since 1997, the deer have been treated each winter across the board with ivermectin (150 mg/kg, CERMIX® pulvis, Biopharm, CZ). Parasites found were the larvae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…In Europe, there are four known species: Cephenemyia stimulator in roe deer ( Capreolus capreolus ); Cephenemyia trompe in reindeer ( Rangifer tarandus ); Cephenemyia auribarbis in red deer ( Cervus elaphus ) and fallow deer ( Dama dama ) (Ruiz et al , ), and Cephenemyia ulrichii in moose or European elk ( Alces alces ). In the last three decades, there have been several studies on the prevalence of C. stimulator larvae in roe deer hunted in different countries such as France (Maes & Boulard, ), Slovakia (Čurlík et al , ), Hungary (Sugár, , ; Király & Egri, ), Poland (Dudziňski, ) and the Czech Republic (Lamka et al , ; Vaca, ; Salaba et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, there are four known species: Cephenemyia stimulator in roe deer ( Capreolus capreolus ); Cephenemyia trompe in reindeer ( Rangifer tarandus ); Cephenemyia auribarbis in red deer ( Cervus elaphus ) and fallow deer ( Dama dama ) (Ruiz et al , ), and Cephenemyia ulrichii in moose or European elk ( Alces alces ). In the last three decades, there have been several studies on the prevalence of C. stimulator larvae in roe deer hunted in different countries such as France (Maes & Boulard, ), Slovakia (Čurlík et al , ), Hungary (Sugár, , ; Király & Egri, ), Poland (Dudziňski, ) and the Czech Republic (Lamka et al , ; Vaca, ; Salaba et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…The chronobiology and descriptive epidemiology of this nasopharyngeal myiasis agent have been investigated by several authors in Europe with partially discordant results (Salaba et al , ). Rainfall in the previous year has been found to positively affect the prevalence and intensity of infestation through its effect on the survival of the pupal stage.…”
Section: Introductionmentioning
confidence: 99%
“…The direct diagnosis of bot fly larval infestation is invasive because it involves necropsy of the head of the host (e.g. Király & Egri, ; Salaba et al , ). Immunodiagnosis of cephenemyiosis by means of enzyme‐linked immunosorbent assay (ELISA) has also been applied (Arias et al , ).…”
mentioning
confidence: 99%
“…Similarly to findings in previous studies (e.g. Salaba et al , ), rhinitis with nasal discharge and muco‐purulent sinusitis were observed in only a few animals. Therefore, it can be assumed that these infestations are generally well tolerated by the animals.…”
mentioning
confidence: 99%
See 1 more Smart Citation